If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.6 + -8x = 2x Solving 1.6 + -8x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1.6 + -8x + -2x = 2x + -2x Combine like terms: -8x + -2x = -10x 1.6 + -10x = 2x + -2x Combine like terms: 2x + -2x = 0 1.6 + -10x = 0 Add '-1.6' to each side of the equation. 1.6 + -1.6 + -10x = 0 + -1.6 Combine like terms: 1.6 + -1.6 = 0.0 0.0 + -10x = 0 + -1.6 -10x = 0 + -1.6 Combine like terms: 0 + -1.6 = -1.6 -10x = -1.6 Divide each side by '-10'. x = 0.16 Simplifying x = 0.16
| 34x^2+154=0 | | 8x^2-17x+47=0 | | -3(m-2)= | | -74=-7x+4(2x-17) | | 15ab+25ab+-12ab= | | 6a-2ab-8-4ab+3a= | | 11-1/3b=-6 | | 3r^2-13r-10=0 | | 21x-12+3=x-31x | | 8(x+9)-21=0 | | Y=20-16x^2+32x | | 3x^2+15x-8=0 | | x^(1/3)=3 | | 3.6=r(24) | | (4-u)(2u-5)=0 | | 8x^2+4x-3-9x^2= | | 3(5-2x)=3(5x+2) | | 7x-9=5x-53 | | 16x^2-3x-4x^2+5+10= | | 9-4(5x-7)= | | x^2+118x-378=0 | | -6x^2+2+11x^2-13-5x= | | 13-52+f=34 | | 6x-1=3y+2 | | 5(c+9)=5(c-4) | | 2(1/3)x3(2/7) | | r^2-3r=2r+14 | | 2lne+3ln(x-1)=5 | | 5y-3+y+41=6y+40-2 | | 9x^2-14x-4+3x= | | x^-2=9/16 | | 24a/4 |